Pedicled omental flaps in the treatment of complex spinal wounds after en bloc resection of spine tumors. Issue 9 (September 2017) - Sambri, Andrea; Gasbarrini, Alessandro; Cialdella, Sergio; De Iaco, Pierandrea; Boriani, Stefano
Summary: Study design: The present paper presents a retrospective study of 5 patients who underwent pedicled omental flap procedure following spine tumor removal. Summary of background data: Postoperative wound dehiscence represents a major complication in spinal surgery, particularly after en bloc tumor resection, because of the extended sacrifice of soft tissues and adjuvant radiation therapy and chemotherapy. Methods: Five patients, with a mean age of 52 years (range, 24–71 years), who underwent omental flaps for the treatment of postoperative complication in spine tumor resections were retrospectively evaluated. Results: Four of 5 patients underwent omental transposition after a mean of 15 months (range, 4–27) from the previous surgery because of dehiscence of the wound (all of them had cerebrospinal fluid leak: 1 transpleural and in 3 cases, associated with deep infection), whereas one patient underwent the omental flap procedure at the time of elective spinal surgery because of several contemporary risk factors for wound healing. At the time of discharge after a mean of 36 days (range, 23–53), all patients had well-healed surgical wounds with an acceptable structural and aesthetic result. One of the patients had ileus, requiring surgical lysis of abdominal adhesions 3 months after omentum flap procedure. No other complications were observed. Conclusion: Our data suggest that pedicled omental flap is a viable option for the treatment of complicated spinal wounds, helping in the resolution of the infection and CSF leak.